Evaluation of Carbon Emission Disclosure with Media Moderation Variables Exposure (Empirical Study on Mining Companies Listed on the Indonesia Stock Exchange 2020-2022) - Mardini, Sasra; Mukhzarudfa, Mukhzarudfa; Olimsar, Fredy (Formosa Journal of Multidisciplinary Research, 2025)
The research examines how carbon emissions in Indonesian mining companies are influenced by three key factors: financial metrics, organizational scale, and oversight through independent commissioners. The analysis focuses on companies registered with the Indonesian Stock Exchange during 2020-2022. Using a numerical-based quantitative approach, the research draws from secondary sources, including corporate annual reports and sustainability documents available through official company websites and the Indonesian Stock Exchange portal. From a total population of 61 listed mining companies, the researchers employed purposive sampling to select 30 companies, yielding 90 data points for analysis. The investigation utilized multiple linear regression techniques, processed through SPSS 26.0 windows software. The findings reveal that neither financial performance nor independent commissioners significantly impact carbon emission levels. However, organizational scale demonstrates a significant inverse relationship with emissions. Regarding media exposure's moderating role, it shows no significant effect on the relationship between financial metrics or organizational scale and carbon emissions. Interestingly, media coverage does moderate the relationship between independent commissioners and emission levels.